2020
DOI: 10.7759/cureus.11574
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitudes Towards Telemedicine Among Medical Students in the United States

Abstract: Introduction: Telemedicine (TM) or telehealth is defined as the delivery of healthcare services at a distance using electronic means. It is a rapidly growing field of medicine that uses telecommunication to provide healthcare services to patients such as the elderly and those in rural locations who may otherwise be unable to make it to the hospital or physician's office. With the rise in the popularity of TM, educating future physicians on this technology will become vital. This study aimed to explore medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…These findings echo a survey of medical students in the United States conducted before the COVID-19 pandemic in which only 20% reported having telemedicine training offered at their medical school, and 43% were unsure whether such training was available. 20 Unfortunately, the majority of IM interns in this study missed clinical time due to the COVID-19 pandemic, a potentially lost opportunity to conduct telehealth training.…”
Section: Discussionmentioning
confidence: 94%
“…These findings echo a survey of medical students in the United States conducted before the COVID-19 pandemic in which only 20% reported having telemedicine training offered at their medical school, and 43% were unsure whether such training was available. 20 Unfortunately, the majority of IM interns in this study missed clinical time due to the COVID-19 pandemic, a potentially lost opportunity to conduct telehealth training.…”
Section: Discussionmentioning
confidence: 94%
“…As reported in previous studies conducted across different communities, the participants in this study showed interest in telehealth. They reported that it was necessary for their education and training and that it provided knowledge and opportunities to develop their skills, which could encourage students to use eHealth techniques in the future [ 25 , 26 ]. Although the interns showed good awareness of digital health apps and positive views regarding the inclusion of digital health technology in their education and training, many of them did not attend additional training in telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those reported by a previous study conducted at the end of 2020 among medical students. The study concluded that only 17.4% of medical students had prior exposure to telehealth despite having a high level of interest in using telehealth in the future [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though medical educators have proposed strategies to ensure the inclusion of learners during this unprecedented time, striking the balance between prioritization of patient and provider safety while keeping trainees engaged has proven to be an ongoing challenge [ 1 ]. Prior to the pandemic, few learners had reported much, if any, clinical experience with telehealth [ 2 ], yet many have now become comfortable and competent in utilizing this modality [ 3 •]. Current telehealth literature from the past year focuses on provider and patient perceptions of telehealth [ 4 ], though fewer studies have focused on its direct impact on trainees’ clinical education.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that, despite the often complex and sensitive nature of interactions with patients, adolescent healthcare can be provided effectively and successfully through telehealth; however, the efficacy of this platform in clinical education has not been fully established [ 5 7 , 8 •, 9 •]. Since the early months of the pandemic, there has been a surge of publications on the importance of including learners in the virtual setting, though the majority of articles have focused on medical and nursing student education, with fewer studies examining the experiences of medical residents or clinical fellows [ 3 •, 10 , 11 , 12 ••]. Several Adolescent Medicine divisions throughout the country have described the challenges, opportunities, and impact of a ramp-up to telehealth in the setting of COVID-19 [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%